The FDI spillover effect on the efficiency and productivity of manufacturing firms: Its implication on open innovation - Lilik Sugiharti; Mohammad Zeqi Yasin; Rudi Purwono; Miguel Angel Esquivias Padilla; Deasy Pane (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
In this study, we investigated the effects of foreign direct investment (FDI) spillovers on firm production and technical efficiency in Indonesia's manufacturing sector from 2010 to 2015. We scrutinized three different channels of horizontal spillover, namely, demonstration, technology adoption, and competition channels. We also captured the heterogeneous effect of firms by categorizing them based on their technological intensity (low, medium, or high). Using time-varying stochastic production frontier analysis, we found that manufacturing firms in each technological group benefit from FDI, either from productivity improvement or technical efficiency improvement. High-technology firms mainly benefit from FDI due to their high technological absorption capability. Meanwhile, medium-high and medium-low tech firms increase productivity through the demonstration effect and the technology adoption channel, despite underperforming in technical efficiency. Finally, low-tech firms, which primarily employ unskilled workers, suffer from large inefficiency. We found that increased FDI, combined with improvements in technology absorption capacity, can help revitalize the productivity of low-tech firms. FDI, firm size, and access to foreign inputs all support production effects but have no direct positive impact on firms' technical efficiency. The results of this study suggest that the government should ensure that domestic firms can absorb the technical capability of a foreign presence. Open innovation can help strengthen foreign-domestic linkages to contribute to growth through the transfer of knowledge, skills, and technologies.
Keywords: 650; demonstration effects; economic globalization; FDI; local economic development; market competition; open innovation; spillovers; technical efficiency; technology adoption